Quebec Trophoblastic Disease Registry: How to Make an Easy-To-Use Dynamic Database. Issue 4 (1st May 2015) - Sauthier, Philippe; Breguet, Magali; Rozenholc, Alexandre; Sauthier, Michaël
Abstract : Objective: To create an easy-to-use dynamic database designed specifically for the Quebec Trophoblastic Disease Registry (RMTQ). Introduction: It is now well established that much of the success in managing trophoblastic diseases comes from the development of national and regional reference centers. Computerized databases allow the optimal use of data stored in these centers. Methods: We have created an electronic data registration system by producing a database using FileMaker Pro 12. It uses 11 external tables associated with a unique identification number for each patient. Each table allows specific data to be recorded, incorporating demographics, diagnosis, automated staging, laboratory values, pathological diagnosis, and imaging parameters. Results: From January 1, 2009, to December 31, 2013, we used our database to register 311 patients with 380 diseases and have seen a 39.2% increase in registrations each year between 2009 and 2012. This database allows the automatic generation of semilogarithmic curves, which take into account β-hCG values as a function of time, complete with graphic markers for applied treatments (chemotherapy, radiotherapy, or surgery). It generates a summary sheet for a synthetic vision in real time. Conclusions: We have created, at a low cost, an easy-to-use database specific to trophoblastic diseases that dynamically integrates staging and monitoring. We propose a 10-step procedure for a successful trophoblastic database. It improves patient care, research, and education on trophoblastic diseases in Quebec and leads to an opportunity for collaboration on a national Canadian registry.